Role of Pharm.D in Better Patient Care: Perspective of Indian Health Care Practitioners - Venkataraman, Rajesh; Rashid, Muhammed; Cherian, Mary; Abraham, Ashna; Islam, Shahinur; Manuel, Gloriya Grifth (Indian Journal of Pharmacy Practice)
Background: Clinical Pharmacists (CP) are less prized in direct patient care compared to both physicians and nurses even though most of the professionals identified that the CP is an inexorable part of the medical team. Objectives: To explore the perception of Health care Practitioners (HCPs) towards the Pharm.D and Services provided by the CPs from the Indian perspective. Methodology: A 10 items questionnaire-based cross-sectional survey was conducted through surveying HCPs including medical, nursing, pharmacy and the academician about their perceptions regarding the Pharm.D program and the clinical pharmacy services providing by the CPs in a tertiary care teaching hospital situated in the south Indian state Karnataka. Results: A total of 130 volunteers participated including 91 medical doctors or students, 6 pharmacists who work in the hospital, 17 nurses, 3 academicians and other 13 didn’t mention their profession. In the study, 91.54% (119) accepted that CPs can play a vital role in improving the medication adherence through the patient counselling and 92.31% (120) HCPs were agreed that CPs can provide appropriate interventions for better patient care. Their efforts in drug interactions and ADRs are really appreciated and 82.31% (107) recommended CP as an integral part of the multidisciplinary health care team. Conclusion: Our research suggests that CPs can be an asset to the health care practice especially in India through partnering the HCPs in better patient care by providing the appropriate interventions. Still, there is an emergent need for more practical emphasised syllabus and curriculum to make the Pharm.D graduates more employable.
Keywords: Pharm.D; Clinical Pharmacy; Health care Professional; Perspective; Patient care Main Text.